GLYCEMIC RESPONSE TO PLEXAL ANESTHESIA IN DENTAL PATIENTS - Alexandra Diaconu; Octavian Dinca; Cristina Padurariu; Mihai Bogdan Bucur; Cristina Padurariu; Cristian Vladan; Alexandru Bucur (Romanian Society of Oral Rehabilitation, 2020)
Aim of the study Glycemic control is vital in the care of diabetes mellitus and is significantly associated with the incidence of clinical complications. This study was conducted to evaluate the glycemic response to local anesthesia with various local anesthetics in patients undergoing tooth extractions. Material and methods A total of 60 patients with diabetes mellitus undergoing tooth extractions were included in this prospective, randomized clinical study. First 30 patients were given 4% articaine HCl with 1:200,000 epinephrine and other 30 patients were given 3% mepivacaine HCl, to carry out tooth extractions. Blood glucose estimations were done at definite intervals (before and after the administration of local anesthetic). Results There were no statistically significant differences in the parameters evaluated in this study. Both groups demonstrated a decrease in blood glucose levels over time. Conclusions According to the results of our study, plexal anesthesia with articaine 4% with epinephrine 1:200,000 was comparably as safe as local anesthetic with standard concentrations of plain 3% mepivacaine in diabetes melitus patients.